Alterations in malondialdehyde levels and superoxide dismutase activity in the sera of occupational workers in Erbil city - Abdullah, Gaylany H.; Ahmed, Sardar N.; Nanakali, Nadir M.; Hassan, Abdul-Qadir A. (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Malondialdehyde is the end product of lipid peroxidation by oxidative stress (free radicals). Superoxide dismutase is one of the important antioxidant enzymes that catalyze conversion of superoxide to hydrogen peroxide. The aim of present study is to measure the serum Malondialdehyde concentration and Superoxide dismutase activity in occupational workers.Methods: A prospective study was carried out from October 2011 to May 2012 in collaboration between clinical biochemistry department at the College of Medicine-Hawler Medical University and chemistry department at the faculty of science and health at Koya University. Total of thirty non-office occupational workers were targeted, who exposed to air and industrial material pollutions, all individuals were healthy and non-alcoholics.Results: The mean value of each of the serum Malondialdehyde concentration and serum Superoxide dismutase activity were significantly higher in occupational workers than that of non-occupational workers.Conclusion: Based on findings of the present study it can be concluded that occupational works elevates the release of Superoxide dismutase enzyme, and also increases lipid peroxidation by reactive oxygen species which in turn causes elevation of Malondialdehyde